2017
DOI: 10.1521/soco.2017.35.6.601
|View full text |Cite
|
Sign up to set email alerts
|

When a Look Is Not Enough: No Evidence for Direct Gaze Facilitating Recovery after Social Exclusion

Abstract: Direct gaze has been suggested to convey inclusion. We hypothesized that receiving direct gaze could alleviate distress caused by social exclusion. In two experiments, participants were first either included or excluded, and then shown a video of a person portraying either direct or downward gaze. Basic need satisfaction was measured immediately after the exclusion manipulation and after viewing the eye gaze stimuli. In Experiment 1, after watching the one-minute eye gaze video and "mentally visualizing" an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, because negative attention is preferred to being ignored (e.g., O’Reilly et al., 2014), even when direct gaze could be perceived as a sign of threat (e.g., when it is accompanied by an angry facial expression; Adams and Kleck, 2005), it might reduce the unpleasant effects of exclusion (Rudert et al., 2017; but see also Syrjämäki et al., 2017). Averted gaze represents a primary cue for communicating ostracism and no opportunity for reconnection with others (Williams et al., 1998) although it can signal a danger approaching or the location of an interesting object.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because negative attention is preferred to being ignored (e.g., O’Reilly et al., 2014), even when direct gaze could be perceived as a sign of threat (e.g., when it is accompanied by an angry facial expression; Adams and Kleck, 2005), it might reduce the unpleasant effects of exclusion (Rudert et al., 2017; but see also Syrjämäki et al., 2017). Averted gaze represents a primary cue for communicating ostracism and no opportunity for reconnection with others (Williams et al., 1998) although it can signal a danger approaching or the location of an interesting object.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the exclusion manipulation did not delay the disengagement of attention from direct gaze. Perhaps excluded individuals do not maintain their attention in faces with direct gaze, because seeing direct gaze may not reduce the affective distress elicited by exclusion (see Syrjämäki et al, 2017). Attending to smiling faces, on the other hand, could be an effective way of regulating one's affective state and therefore many people may have learned to habitually direct their attention toward smiling faces, and maintain their attention in these cues, as a response to exclusion.…”
Section: Exclusion and Attentional Disengagementmentioning
confidence: 99%
“…While evaluations of their gaze directions were modulated by ostracism, it seems unlikely that these changes reflect the participants' willingness to affiliate with these stimulus characters in particular. A recent study found that receiving direct gaze from a picture of a face was not sufficient to make ostracized participants feel reconnected, possibly because pictures are not perceived as potential sources of reinclusion (Syrjämäki, Lyyra, Peltola, & Hietanen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We used an abbreviated basic need and mood questionnaire to ensure a short interval between the ostracism manipulation and the gaze cone task. While we chose the items from a basic need questionnaire that has been found to have a very high intercorrelation among items (αs consistently exceed .90, see Molet et al, 2013;Syrjämäki et al, 2017;Wirth & Williams, 2009;Zadro, Boland, & Richardson, 2006), it should be noted that abbreviating the questionnaire lowers the validity and reliability of the measurements. Thus, our results may be more suggestive than conclusive.…”
Section: Discussionmentioning
confidence: 99%